2022
DOI: 10.1021/acsmaterialsau.2c00044
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for the Relationships between Stability and Functional Properties of Electrochemical Energy Materials

Abstract: The path toward a renewable energy future relies on the development of materials for electrochemical energy technologies that are not only highly functional but also stable. In this Perspective, we will discuss a framework for the relationships between function and stability, starting by revisiting how we measure stability that should focus on changes to the nature and number of active centers (materials stability) together with monitoring how current/potential change over time during operation (reaction durab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…18,26,32 Nonetheless, flow cell ICP-MS studies are limited to low current densi�es, and cannot reproduce all the prac�cal condi�ons occurring in an opera�ng PEMFC device (O 2 par�al pressure and current density, lower rela�ve humidity). 33 In this respect, online gas diffusion electrode (GDE) ICP-MS is an adequate tool to simulate the environment of a PEMFC cathode more realis�cally, and gain PEMFCrelevant durability trends. For instance, Ehelebe et al first demonstrated significantly lower dissolu�on of Pt/C catalysts in GDE configura�on compared to flow cell systems due to varying mass transport condi�ons of Pt species, 34 as previously proposed.…”
Section: Introduc�onmentioning
confidence: 99%
“…18,26,32 Nonetheless, flow cell ICP-MS studies are limited to low current densi�es, and cannot reproduce all the prac�cal condi�ons occurring in an opera�ng PEMFC device (O 2 par�al pressure and current density, lower rela�ve humidity). 33 In this respect, online gas diffusion electrode (GDE) ICP-MS is an adequate tool to simulate the environment of a PEMFC cathode more realis�cally, and gain PEMFCrelevant durability trends. For instance, Ehelebe et al first demonstrated significantly lower dissolu�on of Pt/C catalysts in GDE configura�on compared to flow cell systems due to varying mass transport condi�ons of Pt species, 34 as previously proposed.…”
Section: Introduc�onmentioning
confidence: 99%
“…Growing awareness of the limitations of amperostatic or potentiostatic stability metrics have led to the development of alternative, more catalyst-specific metrics to compare various catalyst candidates. 34 In 2017, Kim and co-workers proposed the activity−stability factor (ASF). 35 Similarly, in 2018 Geiger and co-workers introduced the S-number.…”
Section: Introductionmentioning
confidence: 99%